Influences on undergraduate student civic engagement - Lucas, Taiga; Huse, Eric (University of Wisconsin--Stout. Office of Research and Sponsored Programs, 2017)
Civic engagement is essential to a democratic society, yet today’s youth seem generally apathetic to the idea. Existing research confirms that civic engagement has been dwindling in recent years, so it is in our best interest to act to encourage future students to become civically engaged (Mahatmya & Lohman, 2012). This research investigates the relationship between gender and factors that influence civic engagement in a sample of college students at a Midwestern university. The purpose of this study was to examine this relationship and use results from this study to inform university students, administrators, faculty, staff, and fellow researchers to incorporate it into current course curriculum and future research. The research question in this study was: “What influences male and female undergraduate students’ civic engagement?” We predicted no difference between male and female civic engagement because both have the same components comprising their microsystem, thus the factors that influence students to be civically engaged are the same according to Bronfenbrenner’s Ecological Theory of Development (Bronfenbrenner, 1979 as cited in White & Klein, 2002, p. 216). This hypothesis is based upon evidence from both literature and theory. Paper surveys were administered to 12 undergraduate classrooms. Surveys included 12 statements that were evaluated by students on the Likert scale. Support for the hypothesis is mixed with statistically significant differences for four of the 12 variables. Implications for practitioners include gender specific teaching about civic engagement. Future research would benefit from a random national sample with supplemental qualitative interviews to understand lived experiences.
Research article with tables.
Keywords: social responsibility; citizenship; undergraduate students; civic engagement; Undergraduates--Political activity; Undergraduates--Societies and clubs; Undergraduates; Community and college